OPTIMALISASI PENGELOLAAN KEUANGAN KOTA MANADO: MEMPERKENALKAN INSTRUMEN PUBLIC FINANCIAL MANAGMENT - Victor P. K. Lengkong; Olivia S. Nelwan; Bode Lumanauw (UPT Penerbitan Universitas Jember)
The aims of the study is to introduce an instrumen to evaluate the optimalization of finance management in a region. Survey approach is used trough filling the data instrument of public financial management (PFM) by 9 finance executive representing each region. The method analysis is based on the percentage accompolishement score of each item evaluated using spider net. The result showed that there are few aspect that are already optimal, those are : region regulation availibility, accounting, debt management and public investation, alng with audit implementation and eksternal control. While for the key aspect, it is already good but it need to be optimized, like cash management, supplying inventory and services, audit implementation and external control, planning and budgeting, along with internal controlling. Manajerial implication from the goverment, especially the finance executive,cash management need to be noticed, Concerned to tax and retribution regulation program availibility; supplying inventory and services has to considered about the price difference between the amount of total budget and the realization of APBD year before, it must less than 10%. The internal controlling aspect need to be considered that BAWASDA must has 50% staff who is expert or has accounting education background.